BURUNG STRATA BAWAH (UNDESTORY) DI HUTAN PEGUNUNGAN TAMAN NASIONAL KERINCI SEBLAT (TNKS) KERINCI JAMBI - Fitri, Liza Meini; Handika, Heru; Solina, Inda Dwi (Sainstek : Jurnal Sains dan Teknologi, 2015)
Birds are one of the biological wealth owned by Indonesia. The structure of the lower strata of bird communities in tropical areas represent a very good system to see the difference in sensitivity between species for habitat variation in different scales. This study was conducted in January 2013 using the method of net Mist (mist nets) in the Kerinci National Park (TNKS). Birds that are found as many as 21 species to 83 people only order passerines with six families. The diversity of birds affected by many factors diantarannya abundance of epiphytes, an abundance of fruits, the openness of the forest floor and tree species composition. Generally mountainous forest area will have a relatively high number of species ang.Key word: Undestory, Birds, TNKS